REGISTER IN CAMERA ADVERTISEMENT - NOVEMBIANTO FAHAMZAH, FREDY (Language Horizon: Journal of Language Studies, 2013)
Abstrak Penelitian ini merupakan penelitian sosiolinguistik yang berkonsentrasi pada analisis fenomena register yang digunakan di Canon dan Nikon iklan kamera. Dalam iklan dapat dilihat bahwa ada beberapa istilah yang sulit digunakan untuk menunjukkan spesifikasi, fitur dan nama-nama teknologi yang diterapkan di perangkat kamera Nikon dan Canon. Selain itu, penelitian ini juga menganalisis pemahaman makna register dan pengaruh penggunaan register dalam iklan kamera. Karena penelitian ini bermaksud untuk menganalisis register yang digunakan dalam iklan kamera, pemahaman register oleh konsumen, dan efek dari menggunakan register, maka dalam penelitian ini ditetapkan tiga jenis laporan masalah, yaitu (1) leksikon apa yang digunakan dalam iklan kamera? (2) Bagaimana konsumen mengetahui dan menemukan makna dari register yang digunakan dalam iklan kamera? (3) Apa efek dari menggunakan register dalam iklan kamera? Penelitian ini menggunakan metode kualitatif deskriptif dan metode kuantitatif deskriptif untuk menjawab pertanyaan penelitian. Subyek penelitian ini adalah brosur dari kedua Canon dan Nikon kamera iklan dan konsumen. Mengamati iklan digunakan untuk mendapatkan bentuk kata-kata yang berbeda, sedangkan meminta jawaban konsumen dengan menggunakan kuesioner digunakan untuk mendapatkan data jawaban atas pemahaman register dan efek register itu sendiri. Hasil analisis menunjukkan bahwa ada banyak register yang digunakan dalam iklan kamera dan sebagian besar konsumen tidak tahu tentang register. Mereka cenderung menggunakan beberapa sumber untuk mengetahui arti dari register. Meskipun register hampir tidak dimengerti oleh konsumen, tetapi memiliki beberapa efek. meningkatkan kecenderungan produk dan daya beli adalah efek pertama. Mendesak konsumen untuk membeli dan meningkatkan prospek perusahaan adalah efek kedua dan efek ketiga. Kata kunci: register, iklan, kamera Abstract This study is sociolinguistics study which concentrates on analyzing the phenomena of registers used in Canon and Nikon camera advertisement. In advertisement can be seen that there are some difficult terms used to indicate the specification, features and the names of technology which are applied in Canon and Nikon camera devices. In addition, this study also analyzes the understanding meaning of registers and the effect of using registers in camera advertisement. Because of this study is intend to analyze the registers used in camera advertisement, the understanding of registers by consumer, and the effect of using registers, this study is set out three kinds of statements of the problem, namely (1) What lexicons are used in camera advertisement? (2) How does the consumer know and find out the meaning of registers which are used in camera advertisement? (3) What are the effects of using registers in camera advertisement? This study uses both descriptive qualitative and descriptive quantitative method to answer the research question. The subject of this study is brochure of both Canon and Nikon camera advertisement and consumers. Observing the advertisement is used to get the form of different words, while asking the consumers by using questionaire is used to get data to aswer understanding and effect of registers itself. The result of the analysis shows that there are many registers used in camera advertisement and most of consumers do not know about registers. They tend to use several source to find out the meaning of registers. Although registers is hardly understood by the consumers, but it has several effects. increasing propensity of product and buying power is the first effect. Urging consumers to buy and increasing company prospect are the second and the third effect. Keywords: register, advertisement, camera background study Language is an important way in communication. It is impossible to conduct social cooperation and communication without language. Language makes people understand each other. language is used by human to conduct communication, a medium to express their thought, and differentiate human with animal. The workfield which uses language as communication for example are business and industry. Communication in both of them is the engaging between manufactures and the consumers. The owner of the business company will do everything to attract consumers. It will have impact for profit of the company and the achievement of the company. For more maximum profit needs maximum demands of product, so it makes success for company by advertising products and it is one of the way to attract consumers. Advertisement also makes people to have attention in what product which is advertised. All of the information about the product is brought by the producer by using advertisment. Advertisment also has contribution to offer some products. Identified as the texts or sometimes pictures, advertisement will influence or motivate the public to buy and use the products or services or even to follow the ideas. The information of their products are spread by using appropriate and effective words. Sometimes, some products tend to use their own technical term to mention something. By using advertisment, a product, which is produced by the producer, can be broadcasted to everyone. Nowadays, camera has been used in every daily activities. People use camera for their hobby, for earning money, for framing picture. Camera becomes well-known because of advertisement. The broadband spreading of advertisement increases the number of sale of camera itself. But sometimes the language used in camera advertisement has different type of vocabulary. The used of different lexicon in brochure, as media advertising, is totaly different with other advertisement such as computer advertisement, automotive advertisement. For example CMOS, both of Nikon and Canon use CMOS in their advertisment. CMOS stands for complementary metal oxide semiconductor. That is the name of technology which is applied in image camera sensor. The use of this technology has an impact on the power consumption. Sensor which has CMOS technology needs low static power consumption. In addition, the ability of image sensor is increasing. It has high noise immunity, so the sensor is able to capture pictures even in low light condition. Moreover, between two brands, Nikon and Canon, it also has differences lexicon. For example, DIGIC and EXPEED. DIGIC is used by Canon while EXPEED by Nikon. Both DIGIC and EXPEED describe the name of processor in both Nikon and Canon digital single lens reflex camera. This processor runs all the function of digital single lens reflex camera such as: setting of more or less light which will be captured by image sensor, correcting image sensor, setting of noise reduction, adjusting the sharpness of the image result, managing the framerate conversion, arranging the menu of the face detection, and others. This processor also determines the extent of power that is used in digital single lens reflex camera. It can be seen that The different uses of word or sentence that used in Nikon Camera Advertisment is known as register. The use of register on Nikon Camera Advertisment is very unique and has its characteristics. Moreover, the register used on Nikon Camera Advertisment is different from any other formal written language, such as newsletter, magazine et cetera. This study is concerned with register theory that appears in camera advertisement, the consumer understanding about meaning of registers and the effect of using registers. This study will be interesting because it will focus on the research of different vocabularies on camera advertisement. Moreover, there are so many different used of term on that. It is also interesting to conduct research on photography field, because today photography is the worldwide hobby and they use camera not only for earn money but also to spend their spare time. RESEARCH METHOD This research is a type of descriptive qualitative and descriptive quantitative research. Those methods totally suited to analyze and describe the wider range of statement of the problem and describe and analyze the vocabularies which were used in the camera advertisement. As stated by Greene in Litosellitti, he said that reviewed studies taking a mixed methods approach and argued that combining the two paradigms is benefical for constructing comprehensive accounts and providing answers to a wider range of research questions (2010:30). This thesis clasified and compared vocabularies betweeen Nikon Camera Advertisement with Canon Camera Advertisement. The first one, the general vocabularies were analyzed which are used both on Nikon Camera Advertisement and Canon Camera Advertisement. The specific vocabularies were analyzed secondly, that was from Nikon and Canon Camera Advertisement which has differences with Canon Camera Advertisement. Last, questionaire was used to answer the second and the third statement of the problem. To make the data easy to read, the number of partcipants choosing a certain option was changed into percentage. Formula was used to count percentage of participants toward the answer, it is shown below: The source of data was collected from brochures as document which were taken from both Nikon and Canon Camera Advertisement. From this data it could be concluded that there were some vocabularies which were unknown by others and it could be called as register. Then it was analyzed by using some theories and supporting theories. The second and third were person and place. That is why this thesis used questionaire which was taken from the participants as the person in Surabaya as the place. It took 50 responden to fulfill the questionaire from random sampling area in Surabaya due to answer the second and third research question. DISCUSSION After conducting analyses to answer the first research question, it can be found that different form of words are used in camera advertisement. Those terms basically have spesific meaning. The meaning of the spesific term is obtained by interpreting the terms itself. The form of words which are used in camera advertisement are devided into two main parts. The first one is, terms which have no differences between Canon Camera Advertisement and Nikon Camera Advertisement. It can be seen in table 1 point (1) until (50). For certain term is used in both two different camera advertisement for example: (1) Noise, both Nikon and Canon use same term to describes variation of brightness or color information in images which can be produced by the use of higher level of ISO number to capture the light and will increase with the setting of sensitivity, length of exposure, temperature and et cetera depend on varies of different camera model. The second one is, terms which have differences between Canon Camera Advertisement and Nikon Camera Advertisement as can be seen in table 2 point (1) until (16). It means that the meaning of both camera advertisement are same but the use of terms is different. For example L-Series in Canon and D-Series. It has different form even has same meaning. Those terms mean the name of lens series. In these series of lenses, it has an additional features on it. Canon introduced L Series by adding UD elements. The price of the lenses with symbol L is expensive than lenses without L symbol. While, Nikon introduced D Series for the lenses by adding briliant processor to know the distance of the subject at which the lenses are focused. Because of the additional feature, as L-Series in Canon Lenses, Nikon Lenses with D word have expensive price. No. Terms No. Terms 1. Megapixel 26. Resolution 2. CMOS 27. Dot 3. ISO 28. Wide Viewing Angle 4. Full Frame 29. Viewfinder 5. Noise 30. AF Assist 6. Wide Dynamic Range 31. Hot Shoe 7. F-Stops 32. FTP Server 8. Signal-To-Noise Ratio 33. LAN Connection 9. AF System 34. Bluetooth 10. Aperture 35. GPS 11. Bokeh 36. Manual Focus 12. EV 37. Flash Sync Contact 13. Speed 38. Depth-Of-Field 14. Metering 39. Dioptric Adjustment Knob 15. Exposure 40. Eyepiece 16. Fps 41. White Balance 17. RAW 42. AE Lock 18. Vignette 43. Red Eye Reduction 19. CF Card 44. Eyelevel Pentaprism 20. SD Card 45. Bulb 21. GB 46. Focal Plane 22. Live View 47. Liquid Crystal Monitor 23. Shutter Cycle 48. HDMI 24. Locking Mode 49. Hood 25. Clear View LCD 50. Mirror Lock Up Table 1 List of lexicons used by both Nikon and Canon Camera Advertisement No. Terms by Canon Terms by Nikon Meaning 1. IS VR Blur reduction system 2. EOS F Electronical camera features 3. DIGIC EXPEED Camera image processor 4. USM SWM Faster and silencer autofocus motor 5. CR2/CRW NEF RAW image format 6. Speedlite Speedlight Pop-up camera flashlight 7. SSC SIC Multilayer lens coating 8. DO ED High quality lens glasses 9. UD Elements Aspherical Lens Elements Lens flourite elements 10. EF-S DX Cropping factor image sensor 11. EF FX Full frame image sensor 12. TS-E PC-E Shift and tilt lens movement 13. L-Series D-Series Sophisticated lens with lots of features 14. ALO D-Lighting Brighten image result technology 15. iFCL Metering 3D Matrix Metering Intelligent metering 16. AI-Servo AF-C Continually focussing object Table 2 List of different lexicon which have same meaning used in Nikon and Canon Camera Advertisement Those which are explained above, are terms of different lexicons which form register and could be easily found both Nikon and Canon Camera Advertisement, in contrary with other advertisement which has no same form of terms with camera advertisement. As stated by Trudgill’s (1984) theory, which says that variety of language which linked to occupation, profession, or topic have been termed register. The supporting theories which support registers in camera advertisement are Holmes’s (1992) theory which say that register is used to describe the language of groups of people with common interest of jobs and Wardhaugh’s which state that the use of particular vocabulary is chosen by individual or group. While the way of understanding those terms is based on Hymes (1973) theory which says that the meaning of words can be interpretation of purpose of the first participant. It means that after the terms are found, those are classified in table 1 and 2, after that those terms were interpreted about the meaning of each terms. Question Answers A B C D 17 / 34% 22 / 44% 10 /20 % 1 / 2% 40 / 80% 7 / 14% 1 / 2% _ 12 / 24% 35 / 70% 3 / 6% _ 19 / 38% 5 / 10% 24 / 48% 2 / 4% 11 / 22% 31 / 62% 6 / 12% 2 / 4% 4 / 8% 28 / 56% 6 / 12% 11 / 22% Table 4.3 Participants’ Responses about understanding registers. The second research question results is 35 participants based on the question number (3) in questionaire have known about camera advertisement know camera advertisement from several media such as televison, brochure, internet and et cetera after found the answer in question (4). And most of participants do not know the meaning of the uncommon terms as can be seen in the result of question (5). Question number (6) is used to convey the way of finding meaning from difficult terms in camera advertisement. They use literature book, internet, camera technician in order to find out the meaning of the terms used in camera advertisement. Sumarnek’s (1993) says that advertisement is using several media to deliver the message there are TV shows, internet and brochure as mentioned in the result of questionaire and Shimp Theories are used to clarify the media of advertising. Question Answers A B C D 7. 15 / 30% 29 / 58% 2 / 4% 4 / 8% 8. 30 / 60% 16 / 32% 3 / 6% 1 / 2% 9. 17 / 34% 32 / 64% _ 1 / 2% 10. 32 / 64% 16 / 32% 1 / 2% 1 / 2% Table 4 Participants’ Responses about effect registers. The third research question is the effects of registers in camera advertisement. Based on the results of questions (7) and (9) about the relation of using familiar terms of product can increase the propensity of product and buying power, Canon as the best choice as seen by the use of easier different words. In this case is also reflected by Dyer (1982) theory that the advertisement should use familiar words to helps consumers find the best choice. Based on the result in question (8), the use of different words can urge the reader as consumers to buy the product. It reflects the Kotler’s Theory (2002) that the use of variety language can attract the consumer, as supported by Shutter’s in Arif Zulkarnaen (1992) which says advertising has several purposes, one of them is to urge the reader as the consumer. The last result can be found after conducting the tenth question in questionaire. The use of registers in camera advertisement can increase the company prospects because the use of registers creating exclusive in using the product. So people choose the product and consider to buy. It reflects Shurter’s (1992) theory about the demand of product will increase the company prospect. ABBREVIATION AND ACRONYM CMOS = Complementary Metal Oxide Semiconductor AF = Auto Focus EV = Exposure Value FPS = Frame per second CF = Compact Flash SD = Secure Digital GB = Gigabyte FTP = File Transfer Protocol LAN = Local Area Network GPS = Global Positioning System AE = Auto Exposure HDMI = High Definition Multimedia Interface IS = Image Stabilizer VR = Vibration Reduction USM = Ultrasonic Motor SWM = Silent Wave Motor SSC = Super Spectra Coating SIC = Super Integrated Coating DO = Diffractive Optics ED = Extra-low Dipersion GRATITUTION May Allah be honored for His love and mercy, this journal can be complete. His deepest and most frankly gratitude is conveyed to: Drs. Slamet Setiawan, MA., Ph.D, for the attention and advice for this journal. CONCLUSION Based on the analysis data it can be concluded that There are several kinds of difficult terms which can be registers or not easily understood by people in camera advertisement, both for Nikon and Canon. It concluded that register in both Nikon and Canon camera advertisement divided into two they are; register which has the same forms and register which has differences forms of Nikon and Canon Camera Advertisement. Based on the results, the use of register which has the same forms is dominantly used in both Nikon and Canon Camera Advertisement.The use of difficult terms in camera advertisment makes people to find out the meaning which conveyed by the difficult terms itself. They collect the information about the difficult terms which is used in camera advertisement through some media. The first media which mainly used is internet, then camera technician and the rest is literature books. On the other hand, there are some effect of using registers based on the survey are, it can increase the propensity of product and buying power, can urge the reader as consumers to buy the prodcuts, and the last increase the company prospects. SUGGESTION This study only focuses on the different used of lexicons which can be found in both camera Nikon and Canon, and discover the understanding of registers by the consumers. This study also find out the effect which is caused by registers in camera advertisement. Meanwhile, there are a lot of register which is not stated here. So it is important for future researcher to learn more about linguistic especially registers to perfectly doing same topic to complete this study. From this belief this study suggests for student in State University of Surabaya and the camera users as future researches to explore more about registers in camera in the next study. REFERENCES Arifin, E. Zaenal, Zulkarnaen and Jumariam. 1992. Pemakaian Bahasa Dalam Iklan Berita Dan Papan Reklame. Jakarta: Pusat Pembinaan dan Pengembangan Bahasa Departemen Pendidikan dan Kebudayaan. Arikunto, Suharsini Dr. Prof. 1998. Prosedur Penelitian. Jakarta: Rineka Cipta. Coultas, Amanda. 2003. Language and Social Context.London: Routledge. Dyer, Gillian. 1982. Advertising As Communication. London and New York: Routledge. Ferguson. 2009. Careers in Focus: Advertising and Marketing- 2nd ed. New York: Infobase Publishing. Fletcher, Winston. 2010. Advertising: A Very Short Introduction.New York: Oxford University Press. Holmes, Janet. 1992. An Introduction to Sociolinguistics. London and NewYork: Longman. Hudson. R. A. 1980. Sociolinguistics. Great Britain: Cambridge University Press. Hymes, Dell. 1973. Speech and Language. New York: W. W. Norton and Company, Inc. Kotler, Philip. 2002. Marketing Management, Millenium Edition, Tenth Edition. New Jersey: Prentice-Hall, Inc. Lane, W. Ronald and Russell, J. Thomas. 2001. Advertising: A Framework. New Jersey: Prentice Hall. Litosellitti, Lia. 2010. Research Methods in Linguistics. London: Continuun International Publishing Group. Nababan, P.W.J. 1984. Sosiolinguistik: Suatu Pengantar. Jakarta: PT. Gramedia. O’guinn, Thomas C., A, Chris, and R, Semenik. 2006. Advertising & Integrated Brand Promotion- 4th ed International Student Edition. Mason: Thomson Higher Education. Shimp, Terence A. 2007. Advertising, Promotion, and Other Aspects of Integrated Marketing Communications- 7th ed. Mason: Thomson Higher Education. Spurgeon, Christina. 2008. Advertising And New Media. London and New York: Routledge. Surmanek, Jim. 1993. Introduction to Advertising Media: Research, Planning, and Buying. Chicago: NTC Business Books. Sutherland, Max. 2008. Advertising And The Mind Of The Consumer Revised- 3rd International Edition. Crows Nest: Allen & Unwin. Sutopo, H. B. 2006. Metodologi Penelitian Kuantitatif. Surakarta: Universitas Sebelas Maret Press. Trudgill, P. 1984. Sociolinguistics. In Raja T Nasr (ed), Essential of Linguistic Science. Massachusetts: New-Bury House Publisher Inc. Tuten, Tracy L. 2008. Advertising 2.0 Social Media Marketing in a Web 2.0 World. London: Praeger. Wardaugh, Ronald. 2006. An Introduction to Sociolinguistics- 5th ed. United Kingdom: Blackwell Publishing, Ltd. Wary, A. et al. 1998. Projects In Linguistic: A Practical Guide to Researching Language. China: Edward Arnold (Publisher) Limited. White, Ron. 2003. Click! The No Nonsense Guide to Digital Cameras. Berkeley: Osborne. Yule, George. 2006. The Study of Language- 3th ed. United Kingdom: Cambridge University Press. http://www.allbusiness.com/glossaries/goods-services/4942391-1.html (accessed on Friday, May 10th, 2013 13:10) http://www.cameras.about.com/od/Advanced-Camera-Mode.html (accessed on March 22nd, 2013 18:10) http://www.electronics.howstuffworks.com/cameras-photography/digital/question362.htm (accessed on March 22nd, 2013 17:40) http://www.merriam-webster.com/dictionary/camera (accessed on Thursday, May 16th, 2013 22:21) http://www.nikonusa.com/en/About-Nikon/Corporate-Profile.page (accessed on Saturday, May 18th, 2013 21.42) http://www.webopedia.com/TERM/C/CMOS.html (accessed on March 22nd, 2013 17:20)